Strategi Bauran Pemasaran dalam Meningkatkan Volume Penjualan pada Intentions Coffee: Studi Kasus di Kota Pare - Roisyah Puspa Sari; R. Yuniardi Rusdianto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze the marketing strategies used by Intentions Coffee in Pare City to increase its sales volume. This research method uses a descriptive qualitative approach. The sample determination was carried out purposively by analyzing the 7P marketing mix strategy (product, price, place, promotion, pople, physical evidence, process) that had been determined. This research also uses SWOT analysis (Strength, Weakness, Opportunity, Threat). SWOT analysis is used to evaluate the impact of strengths and weaknesses on the company's environment as well as opportunities and threats on the company's external environment. By analyzing using the SWOT method, it can produce several alternative strategies for making the right decisions to carry out. The results of this research show that Intentions Coffee has an internal strength of 1.86, a weakness of 0.96, an opportunity of 1.38 and a threat of 1.47. In the SWOT analysis diagram, Intentions Coffee is in quadrant position 2 (two) which can support a diversification strategy by optimizing the strength of the threats it has.